2016
DOI: 10.1016/j.jss.2016.06.085
|View full text |Cite
|
Sign up to set email alerts
|

Global microRNA profiling for diagnostic appraisal of melanocytic Spitz tumors

Abstract: Background Melanoma skin cancer remains the leading cause of skin cancer related deaths. Spitz lesions represent a subset of melanocytic skin lesions characterized by epitheloid or spindled melanocytes organized in nests. These lesions occupy a spectrum ranging from benign Spitz and atypical Spitz lesions all the way to malignant Spitz tumors. Appropriate management is reliant on accurate diagnostic classification, yet this effort remains challenging utilizing current light microscopic techniques. The discover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 40 publications
0
14
0
1
Order By: Relevance
“…In this study, we observed that the expression of miR‐21‐5p is up‐regulated in melanoma tissues. Consistently, increased miR‐21 expression has been observed in malignant melanocytic skin tissues compared with benign tumors [12‐14]. Different from the study by Martin del Campo et al .…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In this study, we observed that the expression of miR‐21‐5p is up‐regulated in melanoma tissues. Consistently, increased miR‐21 expression has been observed in malignant melanocytic skin tissues compared with benign tumors [12‐14]. Different from the study by Martin del Campo et al .…”
Section: Discussionmentioning
confidence: 70%
“…Interestingly, increased miR‐21 expression has been observed during the transition from a benign melanocytic lesion to malignant melanoma [12]. Similarly, miR‐21‐5p has been reported to be overexpressed in malignant melanocytic skin tissues compared with benign tumors by global miRNA profiling [13], as well as next‐generation sequencing by Babapoor et al [14] and Latchana et al [2]. Functionally, miR‐21 has been demonstrated to enhance the invasiveness of melanoma cells by inhibition of tissue inhibitor of metalloproteinases 3 [15].…”
mentioning
confidence: 99%
“…In addition, miR-1260b was investigated in malignant melanoma patients, and miR-1260a was reported to show a different expression pattern in the surgical resection follow up of melanoma [64]. mi1260a expression was shown to have higher expression in atypical Spitz lesions compared with the levels in benign Spitz tumors [65]. mi1260b was detected to decrease the cell migration, and invasion in nonsmall cell lung cancer cell strains (A549).…”
Section: Discussionmentioning
confidence: 99%
“…Another miRNA, hsa-miR-484, is involved in apoptosis suppression [49]. Moreover, we decided to include in our quantitative analysis hsa-miR-1260a because of its prognostic value in a few cancer types [50][51][52].…”
Section: Overexpression Of Mcpip1 Protein Does Not Significantly Altementioning
confidence: 99%